A clinical decision support system based on ontology and causal reasoning models / Nur Raidah Rahim, Sharifalillah Nordin and Rosma Mohd Dom - Rahim, Nur Raidah; Nordin, Sharifalillah; Mohd Dom, Rosma (Universiti Teknologi MARA, Perlis, 2019)
Clinical decision support system (CDSS) is promising in assisting physicians for improving decision making process and facilitates healthcare services. In medicine, causality has become the main concern throughout healthcare and decision-making. Causality is necessary for understanding all structures of scientific reasoning and for providing a coherent and sufficient explanation for any event. However, there are lack of existing CDSS that provide causal reasoning for the presented outcomes or decisions. These are necessary for showing reliability of the outcomes, and helping the physicians in making proper decisions. In this study, an ontology-based CDSS model is developed based on several key concepts and features of causality and graphical modeling techniques. For the evaluation process, the Pellet reasoner is used to evaluate the consistency of the developed ontology model. In addition, an evaluation tool known as Ontology Pitfall Scanner is used for validating the ontology model through pitfalls detection. The developed ontology-based CDSS model has potentials to be applied in clinical practice and helping the physicians in decision-making process.